The model of radio broadcasting in the Second Polish Republic. Concepts – struggle for the license – experimental radio of the Polish Radio Technical Society - Kaszuba, Elżbieta (Model radiofonii w II Rzeczpospolitej. Koncepcje – walka o licencję – eksperymentalne radio Polskiego Towarzystwa Radiotechnicznego, 2014)
The Second Polish Republic was re-established as a whole composed of peripheral areas of three powers. In these circumstances, after regaining independence, the idea of restoring unity at various levels became the focus of the Polish raison d’etat. At that time the radio, which at the end of World War I revolutionised communication and the transfer of information, could prove useful in supporting the process of unifying the state and society by means of extensive propaganda campaigns. Two main attitudes were presented in a public debate on the shape of the national radio in Poland. The citizens’ movement promoted a model of the radio as a monopolistic organisation subject to the State, operating on the basis of a license and subscription, responsible for carrying out a mission for the benefit of the state and society.
Społeczeństwo i Ekonomia = Society and Economics, 2014, Nr 1 (1), s. 133-153
Keywords: radio; broadcasting; integration; state; nadawanie programów; integracja; państwo